The impact of risk minimization measures on compliance and prescribing practices of flupirtine in Germany. (2nd January 2019) - Kaplan, Sigal; Ehlken, Birgit; Hamann, Xenia
Abstract: Objective: In response to safety concerns, risk minimization measures (RMM) for flupirtine were implemented in Europe in 2013 to reduce hepatotoxicity risk. This study aims to characterize compliance and prescribing practices of flupirtine before and after RMM implementation. Research design and methods: A retrospective pre–post design cohort study was conducted in the outpatient setting using a longitudinal electronic medical record database in Germany. The study population included patients who initiated flupirtine. One-year pre- and post-implementation periods were assessed. Main outcome measures: Six RMM elements were evaluated, including indication of acute pain, use for maximum of 2 weeks, use when other analgesics are contraindicated, no pre-existing liver disease or alcohol abuse, no concomitant drug induced liver injury, and weekly liver function tests. Results: The number of flupirtine users decreased by 34.4% from 18, 291 in the pre-implementation period (2012) to 12, 000 in the post-implementation period (April 2015 to March 2016). Elements of RMM with substantial improvement included flupirtine prescription duration, where the proportion of patients with duration ≤14 days increased significantly by 16.5% from 74.8% to 91.3% in the pre- and post-implementation periods, respectively. RMM with a moderate-to-high degree of compliance during the post-implementation period, although with a very small or no change from the pre- implementation period, included restriction of flupirtine prescribing to patients with acute pain when other analgesics are contraindicated, and avoiding use in patients with either pre-existing liver disease or concomitant drugs known to have a potential hepatotoxic effect. Weekly liver function tests had a low degree of compliance. Conclusions: These findings demonstrate that, while physicians restricted flupirtine prescriptions to short-term use in the target population of acute pain, not all drug labeling elements were followed to the same extent in routine practice.